INFLUENCE OF INCOME INEQUALITY, ECONOMIC GROWTH, UNEMPLOYMENT ON INDONESIAN POVERTY IN 1992-2019 - Shalsabila Rizky Aureli; Whinarko Juliprijanto (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2022)
Indonesia cannot avoid the issue of poverty because it is a developing nation with a growing population. During the period from 1992 to 2019, the number of poor people in Indonesia fluctuated, fluctuating between increases and decreases each year. Therefore, it is necessary to conduct an analysis in order to determine the factors that contribute to poverty. This study's aims to examine the impact of income inequality, economic growth, and unemployment on poverty in Indonesia between 1992 and 2019. Time series data are utilized. The data utilized for analysis are secondary data from the World Bank and the Central Statistics Agency (hereinafter referred to as BPS). Through the E-views 10 software, the analysis tool employs the Engle Granger-Error Correction Model. The findings indicate that (1) short- and long-term income inequality has a negligible impact on poverty in Indonesia and (2) short- and long-term economic growth has a positive impact on poverty in Indonesia. on the long term, poverty in Indonesia has a significant impact In Indonesia, between 1992 and 2019, unemployment has no significant short-term impact on poverty, but a significant long-term impact.